ANTESEDEN AFFECTIVE COMMITMENT DOSEN TETAP PADA PERGURUAN TINGGI SWASTA DI MADIUN, NGAWI, DAN PONOROGO - Srimulyani, Veronika Agustini (Widya Warta, 2010)
The purpose of this research was to identify the antecedents of affective commitment by testing the direct or indirect impact of job involvement, distributive justice, and significant procedural justice toward affective commitment through job satisfaction as mediating variable. The research subjects were the full-time lecturers of private higher learning institutions in Madiun, Ngawi, and Ponorogo. The sample was 100. The research instrument was questionnaires based on Likert scale on 5 point. The data were analyzed by the use of path analysis by AMOS 5.0 and stepwise multiple regression by SPSS 12.0 package software. The result of path analysis showed that: 1) job involvement, distributive justice, and procedural justice had a significant direct effect on job satisfaction and job satisfaction had a significant direct effect on affective commitment, 2) job involvement had a significant direct effect on affective commitment, 3) job involvement, distributive justice, and procedural justice had a significant indirect effect on affective commitment through job satisfaction as mediating variable.